Boys keep being born : stories - Frank, Joan, 1949- (University of Missouri Press, 2001)
In Boys Keep Being Born, Joan Frank's subject matter and style are stark -- to some, perhaps, shocking. Her collection of stories explores the reverberant mystery of men and women's interactions, touching deeply on those breathtaking, gut-wrenching moments that each of us knows too well, leaving readers dizzy with anticipation, eagerly waiting for more.